AKTOR KOLABORASI DALAM KEGIATAN PASAR RAMADHAN (STUDI KASUS MALAM 29 RAMADHAN DI MAKAM SUNAN AMPEL) - Seftianah, Dina; Septianti, Maudy Dwi; Jati, Della Putri Penivia Setyo; Lova, Adiska Salsabila; Pratiwi, Gita Amalia; Ma'ruf, Muhammad Farid (Publika, 2025)
The Ramadhan Market which is held every year on the night of the 29th of Ramadhan in the Sunan Ampel area of ​​Surabaya is an interesting social phenomenon to study, especially from a collaborative governance perspective. Thousands of visitors from various regions flocked to this area to make a pilgrimage to Sunan Ampel's grave, resulting in a surge in economic activity and community mobility in a short time. This condition demands effective management through collaboration between local government, security forces, business actors, religious leaders and local communities. This research aims to understand how this form of collaboration occurs, the factors that support and hinder it, as well as the potential for more structured policy formulation in the future. This research aims to analyze actor collaboration in managing the Ramadhan Market on the night of 29 Ramadhan in the Sunan Ampel religious area, Surabaya.  This phenomenon is an annual tradition that has an impact on the high concentration of visitors and trade activities on the eve of Eid al-Fitr. This research uses a qualitative approach by utilizing Collaborative Governance theory as an analytical tool. Data collection techniques were carried out through observation, in-depth interviews and documentation. The research results show that collaboration between actors, such as city government, security forces, community leaders and traders, takes place informally and situationally, relying on the experience of previous years. Trust factors, local leadership and shared goals are important elements in maintaining cooperative harmony. However, the absence of a formal policy means that coordination is not yet optimal. Thus, more structural collaborative policy formulation is needed to increase the effectiveness of management of the Sunan Ampel area in the future.